ANALISIS MANAJEMEN SYARIAH PEMANFAATAN PROGRAM DANA DESA UNTUK PEMBANGUNAN DESA DI MASA PANDEMI COVID-19 - Risnawati; Thantawi, Tubagus Rifqy; Mubarok, Mohamad Kharis (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Pasarean Village is a village located in Pamijahan District, Bogor Regency. A common problem that occurs is the reallocation of the use of the Village Fund in 2020 causing many activities or programs to be abolished. This happened because of the Covid-19 pandemic which required the Village Government to allocate Village Funds for the fields of disaster management, emergency and urgent villages, namely to handle and cope with the impact of the Covid-19 pandemic, in this case, namely for Village Cash Direct Assistance (BLT-Desa). Based on the description above, the author is interested in conducting more in-depth research on "Sharia Management of the Utilization of Village Fund Programs for Village Builders during the Covid-19 pandemic" in Pasarean Village, Pamijahan District, Bogor Regency, West Java Province. is how to use the Village Fund Program for Development during the Covid-19 pandemic that occurred in Pasarean Village, Pamijahan District, Bogor Regency. The purpose of this study is to describe and analyze the use of the Village Fund program for Village Cash Social Assistance during the Covid-19 pandemic in the village. Pasarean, Pamijahan District, Bogor Regency. The scope of this research includes : Village Fund planning for BLT-Desa during the Covid-19 pandemic, implementing joint decisions on Village Funds for BLT Desa during the Covid-19 pandemic, administering Village Funds for BLT-Desa during the Covid-19 pandemic, reporting and accountability for Village Funds for BLT-Village during the Covid-19 pandemic. Based on the results of research and data analysis, the authors can draw four conclusions, namely: First, the Village Fund planning process for BLT-Desa is carried out through special village meetings, secondly, in its implementation there are 17 poor criteria used by the Pasarean Village Government, thirdly in administering the Village Fund. for Village BLT, the Pasarean Village Government uses the Village Financial System and the fourth is in reporting and accountability, the Pas Pemdes compiles an LPJ which contains the implementation of BLT-Desa in Pasarean Village.